The Influence of Work Motivation, Team-Work, and Non-Physical Work Environment on Employee Performance at Tajinan Community Health Center - Pramudya, Dimas Fauzan; Adi, Agung Nugroho (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to analyze the influence of work motivation, teamwork, and the non-physical work environment on employee performance at Puskesmas Tajinan, Malang Regency. Design/Methodology/Approach – This study employs a quantitative research approach using multiple linear regression analysis. The population consisted of 64 employees, with the total sampling (census sampling) method applied to obtain comprehensive data representation. Data were collected through structured questionnaires and analyzed using statistical techniques to examine the relationships among the variables. Findings – The results indicate that work motivation has a significant positive effect on employee performance, with intrinsic motivation having a stronger influence than extrinsic motivation. The non-physical work environment also significantly improves performance through interpersonal relationships, organizational culture, and a supportive work climate. However, teamwork does not significantly affect employee performance, suggesting that other factors, such as leadership and workload, may have a greater influence. Originality/Value This study offers empirical evidence from a public health center setting, highlighting the stronger role of motivation and non-physical work environment compared to teamwork. The findings provide a fresh perspective on performance drivers in frontline healthcare units and deliver practical guidance for improving productivity and service quality.